The Influence of Mediation Approaches, Social Factors, and Psychological Factors on Family Dispute Resolution at the Ministry of Religious Affairs in West Java - Masrina Masrina; Ahmad Muzayyin; Muhamad Ammar Muhtadi (Westscience Press, 2023)
This research investigates the influence of mediation approaches, social factors, and psychological factors on the resolution of family disputes at the West Java Ministry of Religious Affairs. Employing a quantitative approach, the study involves a sample of 250 participants and utilizes Structural Equation Modeling with Partial Least Squares (SEM-PLS) for data analysis. The results reveal significant positive relationships between mediation approaches, psychological factors, and social factors with family dispute resolution. The integrated analysis underscores the interplay of these variables, highlighting the importance of culturally sensitive mediation strategies and holistic interventions that address both social and psychological dimensions. The findings contribute to a nuanced understanding of family dispute resolution dynamics in the specific cultural and religious context of West Java, providing valuable insights for policymakers, practitioners, and researchers in the field.